From sovereign impunity to international accountability : the search for justice in a world of states - Thakur, Ramesh, 1948-; Malcontent, Peter (United Nations University Press, 2004)
This book explores the progress, scope, and controversies of holding political leaders accountable for international crimes. The last century has seen the role of law and justice in governance extend beyond the realm of individual nations. Its significance, both regionally and globally, is illustrated by the developments made in international law, especially with regard to the recognition of international human rights, universal jurisdiction, and additional international crimes. However, the significant advances with regard to the international recognition of humanitarian law and the ending of impunity for war criminals stand in real danger of being reversed.